STRATEGI KOMUNIKASI POLITIK PARTAI PDI PERJUANGAN UNTUK MENINGKATKAN KETERWAKILAN PEREMPUAN DALAM PEMILIHAN LEGISLATIF TAHUN 2024-2029 (STUDI KASUS DI KABUPATEN TIMOR TENGAH UTARA) - Taekab, Yosef Kristoforus; Bria, Fridus; Nurak, Ronaldus (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2025)
Abstrack The representation of women in political life is crucial in influencing the policymaking process that impacts women's lives. The role of women in politics is not only to represent women's interests but also to fight for women's rights and to equalize women's status within the social and political context. This study focuses on the strategies used by the PDI Perjuangan in Timor Tengah Utara Regency to increase the representation of women in legislative elections. The aim of this research is to analyze the political communication strategies of PDI Perjuangan to enhance the representation of women in the legislative elections in Timor Tengah Utara Regency. The research was conducted Timor Tengah Utara Regency, Nusa Tenggara Timur Province. The informants in this study include the leadership of PDI Perjuangan in Timor Tengah Utara Regency and the female legislative members of PDI Perjuangan who succeeded in the 2024-2029 legislative elections. This research is descriptive and qualitative in nature, providing results in the form of primary and secondary data. Primary data was collected through observation and in-depth interviews using interview guidelines as a reference. Secondary data was obtained through literature reviews referring to books, previous research, and other studies. The findings show that the representation of women has increased, and the political communication strategies used by the party, such as political education and training, campaigns and lobbying, strengthening networks, and engaging community leaders, have proven effective in increasing women's involvement." Keywords: Women's Representation, Strategy, Political Communication